HMGA2-WIF1 Rearrangements Characterize a Distinctive Subset of Salivary Pleomorphic Adenomas With Prominent Trabecular (Canalicular Adenoma-like) Morphology - Agaimy, Abbas; Ihrler, Stephan; Baněčková, Martina; Costés Martineau, Valérie; Mantsopoulos, Konstantinos; Hartmann, Arndt; Iro, Heinrich; Stoehr, Robert; Skálová, Alena (The American journal of surgical pathology, 2022)
Most of salivary gland neoplasms (benign and malignant) are characterized by recurrent gene fusions. Pleomorphic adenoma (PA), the most frequent salivary gland tumor, is driven by chromosomal rearrangements involving PLAG1 mapped to 8q12 and HMGA2 mapped to 12q13-15 in most cases. Multiple fusion partners have been identified including CTNNB1, FGFR1, LIFR, CHCHD7 and TCEA for PLAG1 fusions and NFIB, WIF1 and FHIT for HMGA2 fusions. To date, no data exist on the morphology of the few reported HMGA2-WIF1-rearranged PAs. We present 28 major salivary gland adenomas displaying distinctive trabecular and canalicular morphology associated with recurrent genotype. Patients were 15 females and 13 males aged 43 to 87 (median: 65). All tumors originated from the parotid. Their size range was 1 to 4 cm (mean: 2.3). Histologically, all tumors showed elongated or columnar cells arranged into bilayered to multilayered communicating and branching strands and trabeculae in a manner similar to canalicular adenoma of minor salivary glands or trabecular myoepithelioma with variable solid confluent intercalated duct-like areas. Fifteen tumors were exclusively canalicular/trabecular while 13 had intermingled or well-demarcated conventional (chondromyxoid) PA component comprising 5 to >50% of the tumor. The monomorphic areas expressed uniformly CK7 (28/28), vimentin (21/21), S100 (24/24), SOX10 (16/17) and variably p63 (8/21) and mammaglobin (6/16) but were negative with p40 (0/24), smooth muscle actin (0/24) and MUC4 (0/16). Targeted RNA sequencing revealed HMGA2 fusions in 14/16 (87%) assessable cases. Fusion partner was WIF1 (12), RPSAP52 (1) and HELB (1). Separate testing of the 2 components in 1 hybrid tumor showed same HMGA2/WIF1 fusion. HMGA2 immunohistochemistry was homogeneously positive in all cases including the 2 fusion-negative cases. A control cohort of 12 genuine canalicular adenomas revealed no HMGA2 fusions (0/4) and lacked HMGA2 immunoreactivity (0/12). This study highlights a distinctive variant in the spectrum of PA characterized by prominent trabecular and canalicular adenoma-like morphology. Our data confirm that canalicular adenomas in major salivary glands (either monomorphic or part of hybrid tumors) are distinct from canalicular adenoma of minor salivary glands. Their uniform genotype irrespective of presence or absence of a conventional PA component argues for classifying those tumors lacking a conventional PA component as "monomorphic variants of PA" rather than canalicular/basal cell adenomas, intercalated duct adenoma, trabecular myoepithelioma or true hybrid tumors.
Keywords: dospělí; Female; Salivary Gland Neoplasms; protein HMGA2; pleomorfní adenom; Adaptor Proteins, Signal Transducing; Adult; genová přestavba; ženské pohlaví; adaptorové proteiny signální transdukční; lidé; Gene Fusion; Aged, 80 and over; nádory slinných žláz; Adenoma, Pleomorphic; Male; nádorové biomarkery; Aged; Gene Rearrangement; fúze genů; Biomarkers, Tumor; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; HMGA2 Protein; Middle Aged; Humans